Eletrólitos mono e multicamadas de céria e zircônia preparados por colagem de fita - Dias, Thiago (Universidade Federal de São Carlos, 2009)
In this work it was investigated bi-layer electrolytes prepared by the tape casting technique. These electrolytes were composed of one layer of 10 mol% gadolinia doped ceria (CDG) and another one of 8 mol% yttria-stabilized zirconia (ZEI -8). CDG tapes were prepared with powder from Fuel Cell Materials (FCM) and powder obtained by oxide mixing. ZEI-8 tapes were prepared with powder from Tosoh Corporation. In the first step, CDG and ZEI-8 tapes were prepared and dense plates were obtained after sintering. Sintered plates were characterized by impedance spectroscopy and scanning electron microscopy (SEM). At 350°C, the highest electrical conductivity of CDG samples prepared with powder obtained by oxide mixing and sintered at 1600 °C was 3.37 x10-4 S.cm-1 and with FCM powder sintered at 1500 °C was 4.33 x10-4 S.cm-1. At the same temperature, ZEI-8 samples sintered at 1600 °C showed 9.6 x10-5 S.cm-1, which agrees with literature results. CDG/ZEI-8 bilayers plates were prepared either by lamination or by double tape casting, followed by sintering at 1600 °C/2 h. Sintered bi-layers prepared by double tape casting were characterized by impedance spectroscopy. Electrical conductivity at 350 °C was 8.82 x10-5 S.cm-1, three times lower than CDG mono layer (3.37 x10-4 S.cm-1) due to high resistivity of CGD/ZEI-8 interface. The bi-layers SEM analysis showed that layers thickness of CDG and ZEI-8, were 140 μm and 24 μm respectively. The adherence between CDG and ZEI-8 layers was attributed to secondary phase in the interface which was responsible for high resistivity of the CGD/ZEI-8 interface.
Mono and multi-layer electrolytes of ceria and zirconia prepared by tape casting
Keywords: Células a combustível; Eletrólitos; Colagem de fita; Céria dopada; Oxido de zircônio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA